Anaerobic mono and co-digestion of food waste and palm oil mill effluent for phosphorus recovery - Rafidah Selaman (2016)
Anaerobic digestion (AD) is a process by which microorganisms break down biodegrable material in the absence of oxygen. The process involves hydrolysis, acedogenesis and methanogensis stages. This technology have gained interests as a technique to recover resources such as energy and nutrient. Additionally, it can help in reducing waste volume as well as greenhouse gases. To improve the production of anaerobic digestion products, co-digestion of different substrates is being introduced. The benefits of co-digestion are to increase the efficiency of digestion process as the co-substrates can supply the missing nutrient in the main substrates. So far, there are no studies have been carried out for applications of anaerobic co-digestion of food waste (FW) with palm oil mill effluent (POME) to recover phosphorus. FW is a type of municipal solid wastes which abundantly available. It has high organic content and can cause various environmental problems if disposed on landfill. While POME is a largest wastewater produced by palm oil mill industry that contain significant nutrient content. It has been reported that phosphorus is a limited and non-renewable mineral source that is essential in our daily life especially for agricultural industry as fertilizers. Therefore, this study aims to investigate phosphorus recovery from FW using anaerobic co-digestion with POME. The physicochemical properties of the samples were determined to study the suitability to be used in anaerobic digestion. The results showed that the total solids and volatile solid of FW and POME were 15%, 3% and 94% and 68%, respectively. pH were, 3 and 5, respectively. These results suggested that FW and POME were appropriate to undergo anaerobic co-digestion for phosphorus recovery. The anaerobic digestion was performed using batch anaerobic digester at mesophilic condition at 37°C (± 1) and pH between 6.8-7.2. Mono-digestion of single FW and POME was carried out to investigate phosphorus recovery at different digestion period for 40 days. It was found the optimum days to recover phosphorus was within 30 days with 89% and 77%, phosphorus recovery from FW and POME, respectively. Therefore, the co-digestion was performed for 30 days at different ratios of FW to POME, namely 70:30% and 30:70%. The results showed co-digestion increased phosphorus recovery to 183-247%, compared to mono-digestion, with 70:30 (FW:POME) was the highest, followed by 30:70 (FW:POME), 100% FW and 100% POME with percentages 247%, 183%, 89% and 77%, respectively. When expressed in mg P/g, the values were, 6.70 mg P/g, 3.00 mg P/g, 4.90 mg P/g and 0.68 mg P/g, respectively. From the results, this study suggested that phosphorus recovery can be improved using co-digestion with FW as the main substrates and POME was a suitable co-substrate in anaerobic co-digestion. While the waste reduction was presented by total solid and volatile solid reduction with 41% and 45%, respectively from the result.